Sources of particle number concentration and noise near London Gatwick Airport. (March 2022) - Tremper, Anja H.; Jephcote, Calvin; Gulliver, John; Hibbs, Leon; Green, David C.; Font, Anna; Priestman, Max; Hansell, Anna L.; Fuller, Gary W.
Graphical abstract: Highlights: Particle size distributions and noise levels were measured at two locations near Gatwick airport in 2018–19. Peak particle number concentrations (PNC) were highest at the site closer to the runway. Source apportionment identified six factors at each site with the airport source factor contributing 17%. The largest source of noise above background was associated with sources of fresh traffic and urban particles depending on the site. PNC is unlikely to be an important confounder in epidemiological studies of aircraft noise and health near airports. Abstract: There is increasing evidence of potential health impacts from both aircraft noise and aircraft-associated ultrafine particles (UFP). Measurements of noise and UFP are however scarce near airports and so their variability and relationship are not well understood. Particle number size distributions and noise levels were measured at two locations near Gatwick airport (UK) in 2018–19 with the aim to characterize particle number concentrations (PNC) and link PNC sources, especially UFP, with noise. Positive Matrix Factorization was used on particle number size distribution to identify these sources. Mean PNC (7500–12, 000 p cm −3 ) were similar to those measured close to a highly trafficked road in central London. Peak PNC (94, 000 p cm −3 ) were highest at the site closer to the runway. The airport source factor contributed 17% to the PNC at both sites and the concentrations were greatest when the respective sites were downwind of the runway. However, the main source of PNC was associated with traffic emissions. At both sites noise levels were above the recommendations by the WHO (World Health Organisation). Regression models of identified UFP sources and noise suggested that the largest source of noise (LAeq-1hr) above background was associated with sources of fresh traffic and urban UFP depending on the site. Noise and UFP correlations were moderate to low suggesting that UFP are unlikely to be an important confounder in epidemiological studies of aircraft noise and health. Correlations between UFP and noise were affected by meteorological factors, which need to be considered in studies of short-term associations between aircraft noise and health.